Persepsi Taruna Terhadap Pembelajaran Menggunakan E-Learning - Oktavera Sulistiana; Nur syam; Muhammad Saleh (Politeknik Pelayaran Barombong, 2021)
The pupose of this study determine the perceptions of cadets towards online distance learning methods. This study used descriptive qualitative method. Perception assessment is carried out by referring to 3 components, namely: components of understanding On Line learning, constraints in taking On Line learning, Suggestions for the Quality of Online learning. Data collection was carried out using an online questionnaire through Google Form to 92 diploma III cadets who were participating in distance learning using purposive random sampling technique. The results showed that the results of several components of distance learning that were given to the respondents, on average, supported and rated positively towards online distance learning methods carried out by cadets